How do sexual violence survivors who must share common social spaces and mutual social relationships with their perpetrators represent their navigation of a secondary victimisation? - Israel, Jahaan (African Studies, 2025)
This research explores the way sexual violence survivors navigate their experiences of secondary victimisation when they have to share social spaces with their perpetrator(s). Existing literature on secondary victimisation primarily focuses on court processes and psychological impacts, highlighting the ways survivors of sexual violence face re- traumatisation in institutional settings. However, there remains limited research on the daily social realities of survivors, specifically their interactions and shared environments with perpetrators, outside of familial contexts. This dissertation addresses this gap by exploring how survivors of sexual violence experience and make sense of these social dynamics, particularly within the context of secondary victimisation. Using qualitative methods, data were collected through in-depth interviews with seven participants who shared their lived experiences. Key findings include the significant impact re-encountering perpetrators has on the emotional wellbeing of victims, social relationships, and how they perform academically; the non-linear nature of the 'aftermath'; and the manner in which victims find solidarity in survivors that have been through something similar. My interviewees shed light on the way e-spaces can be platforms of empowerment (by giving survivors the chance to find community and a place for them to practice their activism) and/or secondary traumatisation (as there is potential for them to be exposed to perpetrators). This study contributes to a deeper understanding of the lived realities of survivors, emphasising the urgent need for supportive interventions that account for the ongoing risks of shared social spaces.